Views among economists: Professional consensus or point-counterpoint? - Roger H. Gordon; Gordon Boyack Dahl (Institute for the Study of Labor (IZA), 2013)
To what degree do economists disagree about key economic questions? To provide evidence, we make use of the responses to a series of questions posed to a distinguished panel of economists put together by the Chicago School of Business. Based on our analysis, we find a broad consensus on these many different economic issues, particularly when the past economic literature on the question is large. Any differences are unrelated to observable characteristics of the Panel members, other than men being slightly more likely to express an opinion. These differences are idiosyncratic, with no support for liberal vs. conservative camps.
Keywords: A11; H0; J0; Z18; 330; consensus among economists